2014
DOI: 10.1007/s11999-014-3672-0
|View full text |Cite
|
Sign up to set email alerts
|

Radial Head Reconstruction in Elbow Fracture-Dislocation: Monopolar or Bipolar Prosthesis?

Abstract: The data from our cadaveric model support the use of either implant type in terrible triad injuries if the collateral ligaments are intact or reconstructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 18 publications
(40 reference statements)
0
17
0
1
Order By: Relevance
“…Conversely, young patients have a high risk of revision surgery after prosthetic head implantation (13). Many artificial radial head designs have been developed, making it possible to choose between monopolar and bipolar versions (14); however, the ideal model for guaranteeing optimal tracking during movement on the capitellum remains to be established (15). Given these considerations, anatomical features of the radius are unique and very difficult to reproduce; moreover, even were a perfect prosthesis available, this should, crucially, be inserted in the correct position (6).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, young patients have a high risk of revision surgery after prosthetic head implantation (13). Many artificial radial head designs have been developed, making it possible to choose between monopolar and bipolar versions (14); however, the ideal model for guaranteeing optimal tracking during movement on the capitellum remains to be established (15). Given these considerations, anatomical features of the radius are unique and very difficult to reproduce; moreover, even were a perfect prosthesis available, this should, crucially, be inserted in the correct position (6).…”
Section: Discussionmentioning
confidence: 99%
“…5-7 Interestingly, a number of studies have found conflicting evidence. In this study, we will summarise our interpretation of the available literature on the basic science of elbow stability.…”
Section: A Few Basic Conceptsmentioning
confidence: 99%
“…Alternatively, a bipolar prosthesis may be used. 5 However, bipolar implants may be more prone to elbow subluxation 14 and also carry the risk of polyethylene wear. Our preference is to use monopolar implants whenever possible.…”
Section: Management Of Individual Structuresmentioning
confidence: 99%
“…Hartzler et al . collected kinematic data on six fresh‐frozen cadaveric upper extremities and concluded that both monopolar and bipolar radial head prostheses are effective in improving valgus and external rotation laxity to the elbow, regardless of coronoid status.…”
Section: Definition Classification and Treatment Principles Of The Tmentioning
confidence: 99%
“…He also pointed out that, because these injuries are commonly seen in younger patients, longer-term studies are needed to determine whether the apparent benefits of radial head arthroplasty are offset by late complications of arthroplasty, such as loosening. Hartzler et al collected kinematic data on six fresh-frozen cadaveric upper extremities and concluded that both monopolar and bipolar radial head prostheses are effective in improving valgus and external rotation laxity to the elbow, regardless of coronoid status 16 .…”
Section: Classification and Treatment Principles Of Radial Head Fractmentioning
confidence: 99%